Characterization of Cell Wall Compositions of Sodium Azide-Induced Brittle Mutant Lines in IR64 Variety and Its Potential Application - Sawasdee, Anuchart; Tsai, Tsung-Han; Chang, Yi-Hsin; Shrestha, Jeevan Kumar; Lin, Meng-Chun; Chiang, Hsin-I; Wang, Chang-Sheng (Plants (Basel), 2024)
The rice brittle culm is a cell wall composition changed mutant suitable for studying mechanical strength in rice. However, a thorough investigation of brittle culm has been limited due to the lack of diverse brittle mutants on similar genetic backgrounds in cell walls. In this study, we obtained 45 various brittle mutant lines (BMLs) from the IR64 mutant pool induced by sodium azide mutagenesis using the finger-bending method and texture profile analysis. The first scoring method was established to differentiate the levels of brittleness in rice tissues. The variation of cell wall compositions of BMLs showed that the brittleness in rice primarily correlated with cellulose content supported by high correlation coefficients (R = −0.78) and principal component analysis (PCA = 81.7%). As demonstrated using PCA, lower correlation with brittleness, hemicellulose, lignin, and silica were identified as minor contributors to the overall balance of cell wall compositions and brittleness. The analysis of hydrolysis and feeding indexes highlighted the importance of diversities of brittleness and cell wall compositions of BMLs and their potential applications in ruminant animals and making bioenergy. These results contributed to the comprehension of brittleness and mechanical strength in rice and also extended the applications of rice straw.